COLLECTIVE LEADERSHIP: A Case Study of the All Blacks - Thomas Johnson; Andrew J Martin; Farah R Palmer; Geoffrey Watson; Phil Ramsey (APMBA (Asia Pacific Management and Business Application), 2012)
This case study evaluates the development of a formal collective leadership approach by the All Blacks (New Zealand’s national men’s rugby team) management. The All Blacks have an astonishing 75% winning record in test matches over a hundred year period. This winning ethos is part of their organizational culture, which has been developed, nurtured and sustained since the inception of the first national team in 1903 (Palenski, 2003; Tobin, 2005).In this qualitative research study, primary data was obtained through the analysis of semi-structured, in-depth interviews with past and present All Black captains and coaches (over a period of 60 years from 1950-2010). Stories which are narratives based on true events provide a rich description, which enhances the credibility and transferability of the findings.A key finding is the strong senior collective leadership that has been ever present. Originally led by senior players informally from ‘the back seat of the bus’ this internal leadership has been formalised by the most recent coaching team and has proved to be very effective with regards to maintaining a winning culture in an ever-changing organizational and socio-cultural environment. The learning culture and learning leadership demonstrated within the All Blacks collective leadership model instils a commitment to total honesty in self and team evaluation and reflection. It is anticipated that these findings will be transferable to other business and team sport contexts and assist in organizational development.